Islamic criminal law in the Malaysian federal structure: a constitutional perspective - Ab Aziz, Shamrahayu (International Islamic University Malaysia, 2007)
States in a federal type of government are allowed a certain amount of autonomy. Under the Malaysian federal structure Islamic criminal law has been put under state jurisdiction. Despite this clear position various questions pertaining to the state jurisdiction on Islamic criminal have recently been raised. This article seeks to discuss those issues in the light of the relevant constitutional provisions and judicial decisions.